The impact of smoking on tuberculosis treatment outcomes: a meta-analysis - Wang, E Y; Arrazola, R A; Mathema, B; Ahluwalia, I B; Mase, S R (The international journal of tuberculosis and lung disease, 2020)
Cigarette smoking contributes to tuberculosis (TB) epidemiology. However, limited evidence exists on how smoking impacts TB treatment outcomes such as treatment loss to follow-up and culture conversion. This meta-analysis assessed current evidence of the impact of active cigarette smoking on TB treatment outcomes. PubMed, Scopus, Embase, and the Cochrane Library were searched for English-language articles published from database inception through 2017. Articles addressing active pulmonary TB and cigarette smoking were identified and data abstracted. Smokers were defined as those who smoked every day or some days at the time of interview/diagnosis. Non-smokers did not smoke at the time of interview/diagnosis. Unfavorable outcomes included any outcome other than cure or completion of TB treatment. Three different data sets were examined: 8 articles addressing unfavorable treatment outcomes, 9 analyzing only treatment loss to follow-up, and 5 addressing delayed smear or culture conversion. Studies that had <20 subjects or that addressed only populations with comorbidities were excluded. We identified 1030 studies; 21 studies fulfilled the inclusion/exclusion criteria. Smokers had greater odds of unfavorable outcomes (pooled odds ratio [pOR] 1.23, 95%CI 1.14-1.33), delayed smear or culture conversion (pOR 1.55, 95%CI 1.04-2.07), and treatment loss to follow-up (pOR 1.35, 95%CI 1.21-1.50). Cigarette smoking is associated with negative treatment results and delayed conversion to negative smear or culture, suggesting smoking is an important factor for consideration in TB elimination efforts.